Managing Expatriates in China A Language and Identity Perspective - Zhang, Ling Eleanor; Harzing, Anne-Wil; Fan, Shea Xuejiao (Palgrave Studies in Chinese Management, 2018)
XV, 225 p. 8 illus., 7 illus. in color.